International business diplomacy - Ruël, Huub (Emerald Publishing Limited, 2017)
Multinational enterprises (MNEs) experienced 'golden days' during the 1990s and 2000s, they expanded globally and were major players in globalization. Today they have become powerful actors in the global economy. CEOs of international businesses are welcomed by heads of state as their counterparts, they are invited by governments to help solve global issues such as climate change and poverty, and they are facing dilemmas comparable to those of other international actors. However, MNEs are facing global legitimacy challenges. They are suspected of tax avoidance, using low wage countries for corporate benefits only, disrespecting privacy regulations, abusing consumer data, violating local community rights, exploiting natural resources, ignoring basic human rights, and employing too many lobbyists targeting national and international political decision-making processes for their own corporate interests.
Obsahuje index.
Keywords: nadnárodní společnosti; podnikání; mezinárodní hospodářské vztahy; ekonomická diplomacie; international business enterprises; business; international economic relations; economic diplomacy; kolektivní monografie; elektronické knihy; collective monographs; electronic books